AB0072 BIOMARKER CHANGES FOR PATIENTS WITH RHEUMATOID ARTHRITIS RECEIVING TOFACITINIB WITH METHOTREXATE OR GLUCOCORTICOIDS VS TOFACITINIB MONOTHERAPY. (June 2019) - Lee, Julie; Chen, Xing; Zhang, Weidong; Martin, David; Hyde, Craig; Hirose, Tomohiro; Shah, Shweta; Fitz, Lori
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of RA. Herpes zoster is more common in patients (pts) with RA vs the general population. 1 This risk increases with tofacitinib use 2 and appears to be further increased with concomitant use of csDMARDs such as methotrexate (MTX), or glucocorticoids (GC). 3 The mechanism for these increases in risk may be linked to treatment-induced interferon (IFN) suppression, 3 given that replication of the varicella zoster virus appears to be limited by IFN activity. 4 Objectives: To evaluate whether treatment of RA with tofacitinib + MTX or GC suppresses IFN pathway proteins to a greater extent than treatment with tofacitinib monotherapy. Methods: This was a post hoc analysis of pooled data from 1 Phase (P)2 (Japan study [NCT00687193 ]) and 2 P3 (ORAL Scan [NCT00847613 ]; ORAL Start [NCT01039688 ]) tofacitinib studies. Serum samples were collected at baseline (BL), Week (W)12 and/or W24 from pts with RA treated with tofacitinib 5 or 10 mg BID, given as monotherapy (Japan study; ORAL Start) or with stable doses of MTX (15–25 mg weekly for ≥6 weeks; ORAL Scan) and/or GC (≤10 mg/day prednisone or equivalent; all studies). A total of 376 proteins associated with cellular and inflammatory processes, including 6 IFN pathway proteins (CXCL10, CXCL9, CXCL11, IL-12, IFNγ and IL-20), were measured using a homogeneous solution-based assay (Olink Proseek ® Multiplex Assay, Uppsala, Sweden). Changes in protein levels from BL to W12 (Japan study, ORAL Scan) and/or W24 (ORAL Scan, ORAL Start) were compared for tofacitinib monotherapy vs tofacitinib + MTX or GC using linear regression models. The dependent variable was change from BL in protein levels at W12 or W24. The independent variable was MTX or GC status. Age, gender, GC status (in MTX model) and BL protein levels and tofacitinib dose were covariates. Regressions were performed separately for each study; results for GC were combined via meta-analysis using fixed and random effect models. Significance was considered at p<0.1 after controlling for false discovery rate (FDR). Data quality control included accounting for plate/batch defects and limits of detection, and removal of sample/analytes with excessive missing data. Results: In total, 659 serum samples were collected from 321 pts. Of the 6 IFN pathway proteins, 2 (IFNγ and IL-20) were below the limit of detection. There was no strong evidence suggesting statistical differences between tofacitinib monotherapy and tofacitinib + MTX or GC in changes in levels of the 4 detectable IFN pathway proteins (CXCL10, CXCL9, CXCL11 and IL-12) from BL to W12 and/or W24. Significant differences were observed for 2 of the 370 other proteins: MMP-1 (FDR adjusted p=0.08) and IL1Ra (FDR adjusted p=0.09), where levels decreased from BL to W12 for tofacitinib + MTX to a greater extent than for tofacitinib monotherapy. Conclusion: The results of this post hoc analysis suggest that tofacitinib + MTX or GC may not suppress circulating serum levels of IFN pathway proteins to a greater extent than tofacitinib monotherapy. Although there were differences at W12 for tofacitinib + MTX vs tofacitinib monotherapy in MMP-1 and IL1Ra, it is not yet clear whether these observations may be attributable to differences in the ethnicities of the study populations receiving these two treatment regimens (global vs Japan). Further analyses of biomarker changes with tofacitinib are ongoing. References: [1] McDonald JR, et al. Clin Infect Dis2009; 48: 1364-71. [2] Winthrop KL, et al. Arthritis Rheumatol2014; 66: 2675-84. [3] Winthrop KL, et al. Arthritis Rheumatol2017; 69: 1960-8. [4] Ku CC, et al. Cell Biosc2016; 6: 21. Acknowledgement: Study sponsored by Pfizer Inc. Medical writing support was provided by Sarah Piggott of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Julie Lee Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Xing Chen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Weidong Zhang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, David Martin Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Craig Hyde Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Tomohiro Hirose Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Shweta Shah Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Lori Fitz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc